1996
DOI: 10.1210/jcem.81.2.8636277
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of insulin-like growth factors and their binding proteins by human normal and hyperplastic prostatic cells in primary culture.

Abstract: Benign prostatic hyperplasia (BPH) is the most common benign proliferative disorder of unknown etiology found in men. Because insulin-like growth factors (IGFs) with their binding proteins (IGFBPs) are involved in the control of cellular proliferation, differentiation, and metabolism, we compared their secretion by prostatic epithelial and stromal cells in primary culture from the four different zones of normal prostate and from hyperplastic tissue to assess their contributions to the hyperplastic development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…IGF-I [20][21][22][23] is functionally homologous to insulin. Its mitogenic effect is due to its ability to facilitate transfer of cells from the G1 to the S phase of the cell cycle.…”
Section: Insulin-like Growth Factor-i (Igf-i)mentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-I [20][21][22][23] is functionally homologous to insulin. Its mitogenic effect is due to its ability to facilitate transfer of cells from the G1 to the S phase of the cell cycle.…”
Section: Insulin-like Growth Factor-i (Igf-i)mentioning
confidence: 99%
“…Tennant et al [24] found that the source of the IGF receptor ligand in the prostate may be the prostatic stromal cells, since in vitro studies showed that IGF-II is produced by stromal cells but not by normal prostatic epithelial cells. Recent data of Boudon et al [21] suggest that prostate epithelial cells may also be the site of IGF-II production. IGF-I mRNA and protein have been detected in BPH stroma, but no IGF-I mRNA or protein has been found in BPH epithelial cells.…”
mentioning
confidence: 99%
“…Prostatic epithelial and stromal cells express IGF-I receptors (IGF-IR) and are responsive to IGF-I (4)(5)(6). In addition to their involvement in normal cell growth, IGF-IR seem to play a crucial role in tumor transformation and the survival of tumor cells through their interactions with oncogenes and tumor suppressor genes (7), and through regulation of metalloproteinases synthesis and tumor invasion and metastasis (8).…”
Section: Introductionmentioning
confidence: 99%
“…9 The transgenic adenocarcinoma prostate model in mice involves elevated prostatic IGF-I mRNA expression that correlates with tumor progression, and serum IGF-I levels in these mice are elevated compared with the levels in nontransgenic animals. 10 It has been shown that prostate cells and tissues contain IGF-I and IGF-II proteins 7,[11][12][13] as well as IGF mRNA, 12,14 -19 IGF-I receptor, 14,15 and IG-FBP-2-IGFBP-6. In addition to the modulation of IGF availability and action, it has been shown that IGFBPs inhibit cellular growth 18,20 -22 and IGF-I receptor activation.…”
mentioning
confidence: 99%